Perception of Breeders and Farmers Regarding Participatory Plant Breeding Programme and its Problems in Punjab - Faisal, Hassamuddin; Kaur, Manmeet; Anand, Anupam (Indian Journal of Extension Education, 2020)
The study was undertaken to analyze the perception of breeders and farmers towards Participatory Plant Breeding in Punjab and to also determine the problems as perceived by the breeders and farmers regarding Participatory Plant Breeding in Punjab. The study was conducted in Punjab Agricultural University, Ludhiana and its research stations in different districts. The study comprised of two kinds of respondents viz. Breeders and Farmers. The total sample size was of 100, 50 breeders and 50 farmers who were randomly selected to take their perception regarding Participatory Plant Breeding in Punjab. Perception and Problems were measured on three-point continuum defined separately for each respectively. Majority of the farmers as well as the breeders agreed that the PPB will improve the rate of adoption of the varieties among the farmers, increase the farmers' organizational and social participation, increase resource poor farmers' access to improved varieties and allow the farmers with freedom of choice of traits in the varieties of the crops. Based on the findings of the study a PPB programme can be devised which can be tested for its feasibility and future prospects in crop improvement and diversification programmes.